THE SYNERGY BETWEEN CORPORATE GOVERNANCE AND PROJECT MANAGEMENT IN LOCAL SELF-GOVERNMENT: THEORETICAL AND METHODOLOGICAL FOUNDATIONS - Rovynska, Kateryna (Public Management and Policy, 2026)
This article examines the theoretical and methodological foundations of the synergy between corporate governance and project management within the system of local self-government. The relevance of the study stems from the need to improve the management of territorial communities under conditions of decentralization, limited resources, and growing demands for more effective managerial decision-making. Particular attention is given to the evolution of corporate governance and project management, as well as to the possibilities of their integration in the public sector. The study aims to substantiate the theoretical and methodological foundations of the synergy between corporate governance and project management and to develop a conceptual model for their integration into the management system of territorial communities. The research employs systemic, structural-functional, comparative, and conceptual methods, which made it possible to carry out a comprehensive analysis of contemporary approaches to organizing management processes. The findings show that the evolution of corporate governance from a control-oriented system to a model of good governance, together with the shift of project management from standardized to adaptive models, creates favorable conditions for their integration. The key points of intersection between strategic, project, and corporate governance have been identified, including the transformation of strategic planning into a project portfolio, accountability through monitoring and evaluation, and the involvement of the local community in decision-making. The article introduces the author’s concept of a “corporate-project model of community management” and presents a conceptual integration model based on the interaction of strategic, monitoring-and-regulatory, and social dimensions of governance. The proposed model contributes to greater coherence in managerial decisions, more efficient resource use, and stronger trust in local self-government bodies. The conclusions indicate that the implementation of a corporate-project model of community management is a promising direction for the modernization of public administration. Further research should focus on methodological approaches to assessing the effectiveness of this model, as well as its adaptation to martial law conditions and post-war recovery.